Perumusan Strategi Bisnis untuk Meningkatkan Daya Saing pada Toko Bangunan XYZ - Nianzhi Nianzhi (Universitas Tarumanagara, 2020)
This research was conducted to find out what business strategies are the most appropriate for XYZ Building Stores to use to compete with other building retail stores. This study applies a qualitative method, by conducting interviews and observations by directly reviewing the subject of the study. The analytical method carried out consists of input stage, mathcing stage, and decision stage. Data that has been collected from the XYZ Building Shop is included in the input stage which consists of an EFE matrix and an IFE matrix. The matching stage that consisting of SWOT matrix, will focus on creating alternative strategies. The decision stage uses QSPM to determine the most appropriate strategy for XYZ building stores objectively. After analyzing the existing data, it is known that the market penetration strategy is the most appropriate strategy for XYZ building stores, besides that the market development strategy can also be chosen because the scores obtained by the two strategies are not too far apart.